Quantification of protein isoforms in mesenchymal stem cells by reductive dimethylation of lysines in intact proteins - She, Yi-Min (WILEY-VCH Verlag, 2012)
Mass spectrometry (MS)-based quantification of highly homologous proteins in complex samples has proven difficult due to subtle sequence variations and the wide dynamic range of protein isoforms present. Herein, we report the use of reductive dimethylation on intact proteins to quantitatively compare protein isoform expression in the nucleus and cytoplasm of mesenchymal stem cells (MSC) and normal stroma. By coupling fixed-charge MS/MS scanning, high-resolution UPLC FT-MS data-dependent acquisition and MASCOT-based data mining, hydrogen/deuterium-labeled dimethyl-lysine peptides were simultaneously captured allowing the accurate comparison of 123 protein isoforms in parallel LC MS/MS runs. Thirty-four isoforms were identified that had expression levels specific to MSC. Where possible, proteomic analyses were verified by Western blotting and were demonstrated to be divergent from the level of gene transcription detected for certain proteins. Our analysis provides a protein isoform signature specific to MSC and demonstrates the suitability of dimethyl-lysine labeling on intact proteins for quantifying highly homologous proteins on a proteome-wide scale.